Anti-dumping regulations: Anti-competitive and anti-export - David R. Collie; Vo Phuong Mai Le (Cardiff University, Cardiff Business School, 2008)
In a Bertrand duopoly model, it is shown that an anti-dumping regulation can be strategically exploited by the domestic firm to reduce the degree of competition in the domestic market. The domestic firm commits not to export to the foreign market which gives the foreign firm a monopoly in its own market. As a result the foreign firm will increase its price allowing the domestic firm to increase its price and its profits. If the products are sufficiently close substitutes then the higher profits in the domestic market are large enough to compensate for the loss of profits on exports.
Keywords: F13; L13; 330; anti-dumping regulations; Bertrand oligopoly; strategic behaviour; Wettbewerbspolitik; Antidumping; Duopol; Betriebliche Preispolitik; Wohlfahrtsanalyse; Theorie